Programming with GitHub Copilot write better code--faster! - Dowswell, Kurt (Tech today, 2024)
In Programming with GitHub Copilot: Write Better Code-Faster, veteran software developer and GitHub community hero Kurt Dowswell delivers an insightful and hands-on exploration of GitHub's powerful, new AI coding assistant, Copilot. In the book, you'll discover how to use the tool's capabilities to push the boundaries of what you thought was possible in programming. Even if you've used autocomplete tools-like VS Code's TabNine extension-before, you'll be floored by GitHub Copilot's potential to transform the way you code. You'll learn how to install, configure, and use the software, from employing it's most common and widely used features to deploying business and enterprise functionality. You'll even discover how to fix runtime and compilation bugs and write unit, integration, and end-to-end tests.